2023
DOI: 10.1097/psy.0000000000001224
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Stress Associations With Blood Pressure: An Ecological Momentary Assessment Study on an App-Based Platform

Abstract: Objective: This study examined the within-and between-person associations of acute and chronic stress with blood pressure (BP) and heart rate (HR) using an app-based research platform. Methods: We examined data from 31,964 adults (aged 18-90 years) in an app-based ecological momentary assessment study that used a research-validated optic sensor to measure BP. Results: Within-person associations revealed that moments with (versus without) acute stress exposure were associated with higher systolic (SBP; b = 1.54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…If they selected "no," they answered questions about stress, perceived coping, and positive emotions in the same manner as in Studies 1-2. In the majority of check-ins (.84%), people selected "no," so consistent with previous papers, our analyses focused on the latter questions (Mak et al, 2023;Newman et al, 2023;Park et al, 2023).…”
Section: Psychological Measuressupporting
confidence: 56%
See 1 more Smart Citation
“…If they selected "no," they answered questions about stress, perceived coping, and positive emotions in the same manner as in Studies 1-2. In the majority of check-ins (.84%), people selected "no," so consistent with previous papers, our analyses focused on the latter questions (Mak et al, 2023;Newman et al, 2023;Park et al, 2023).…”
Section: Psychological Measuressupporting
confidence: 56%
“…Participants were volunteers who downloaded an app called MyBPLab (https://mybplab.com) from the Google Play Store on their Samsung phone and agreed to participate in a 3-week study about people’s stress, emotional experiences, HR, and blood pressure. These data from MyBPLab were collected as part of a larger project, and some additional papers that address distinct questions from the present study have been published previously (Don et al, 2023; Mak et al, 2023; Newman, Gordon, & Mendes, 2021; Newman et al, 2023; Park et al, 2023). As part of the study, they received notifications to complete three check-ins per day (once in the morning, afternoon, and evening).…”
Section: Methodsmentioning
confidence: 99%
“…Research also shows that experiencing daily stressors leads to heightened daily physiological arousal. Mak et al (2023) published results from a large ecological momentary assessment study of 32,169 adults, with nearly 500,000 momentary responses, using both self-report items and physiology collected via optic sensors in a watch or smartphone. Analyses of these data found that participants with more frequent reports of daily stressors had higher than average heart rate and blood pressure across 3 weeks.…”
Section: Section 1: Stress Processes In Daily Lifementioning
confidence: 99%